The relationship between PG-SGA scores and nutritional status of patients receiving chemotherapy - Baş, Dilşat; Sönmez, Özlem; Öngen, Nilay; Şenocak Taşçı, Elif (Progress in Nutrition, 2022)
Background: We aimed to examine cancer patients receiving chemotherapy in terms of nutritional education status, malnutrition rate, and use of oral nutritional support. The relationships between these variables are explored.Materials/Methods: PG-SGA malnutrition screening tool and questionnaires about nutrition education status and oral nutritional support were carried out with 281 cancer patients treated in the chemotherapy unit of a private health institution. The data were analyzed with SPSS.Results: We found that 56.1% of the patients received their nutritional information from the doctor. There was not a significant relationship between nutritional education status and malnutrition. According to the PG-SGA evaluation, 37.7% of the patients were moderately malnourished and 6.8% were severely malnourished. However, it is seen that 72.5% of malnourished patients do not receive oral nutritional support. The PG-SGA results revealed that Albumin was significantly lower in patients with severe malnutrition compared to other groups. It was found that malnutrition was overlooked in 82% of patients evaluated with BMI alone.Conclusion: PG-SGA is a tool that should be used routinely with chemotherapy patients. In future research, the validity of the PG-SGA short form should be conducted as it may provide ease of application and widespread use.